Posterior Vitreous Detachment and Risk of Neovascular Glaucoma in Eyes with Prior Retinal Vascular Occlusions - Laura D. Palmer; Jared D. Peterson; Joni K. Evans; Mark H. Nelson; Sanjay Asrani; Atalie C. Thompson (Ophthalmology and Therapy)
Abstract Introduction To investigate the impact of posterior vitreous detachment (PVD) on the risk of developing neovascular glaucoma (NVG) in eyes with occlusions of the retinal artery (RAO) or retinal vein (RVO). Methods Single-center retrospective case-control study of adults with a history of RVO/RAO. Cases (N = 101) who developed NVG were age and sex matched 1:2 to controls who did not develop NVG (N = 202). Multivariable logistic regression was used to estimate the association between history of PVD and risk of NVG while controlling for other related demographic or clinical factors. Results In initial bivariate analyses, there was no difference in risk of NVG based on eye, lens status, hypertension, history of panretinal photocoagulation (PRP), or retinal surgery (all p > 0.10), a borderline difference based on diabetic retinopathy (DR) (p = 0.06) and prior anti-vascular endothelial growth factor (anti-VEGF) treatment (p = 0.08), and a significant difference based on race/ethnicity, type of vascular event, and PVD status (all p < 0.05). In the final multivariable model, patients without PVD were significantly more likely to develop NVG (OR = 3.07, p = 0.0001) independent of the other covariates. Risk of NVG was greater in those with DR (OR = 1.98, p = 0.0440) and in those with central RVO vs. branch RVO/hemiretinal RVO (OR = 5.77, p < 0.0001). Non-White/Non-Hispanics (OR = 2.56, p = 0.0051) and Hispanics (OR = 3.65, p = 0.0288) were more likely than White patients to develop NVG. Conclusions Progression to NVG after retinal vascular occlusion is more likely in Non-White/Hispanic patients, those with concomitant DR, and those with CRVO/CRAO. The absence of PVD increases the risk for NVG. Further studies are necessary to understand this relationship.